PENGARUH PERAN GANDA DAN KELELAHAN EMOSIONAL TERHADAP KOMITMEN ORGANISASI PADA BOLLY DEPARTEMEN STORE DI BIMA - Jaenab, Jaenab; Firmansyah Kusumayadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The aim of this study was to identify and analyze the effect of multiple roles and emotional exhaustion on organizational commitment at the Bolly department store in Bima so that they can provide input to the leaders at the Bolly department store in Bima. This research is a quantitative research and the type of research is associative with the population in this study being all married female employees, so the sampling technique is a saturated sample of 33 respondents while the data collection technique uses observation, interviews, literature and questionnaires, with reference to the scale Likert 5 points were then distributed to 33 respondents with the status of female permanent employees who are already married at the Bolly Department Store in Bima. The analytical method used in this study is multiple linear regression and then analyzed with SPSS version 20 for windows. The results of this study are: 1) There is no significant effect of multiple roles on organizational commitment at the Bolly Department Store in Bima. 2) There is a significant effect of Emotional Exhaustion on Organizational Commitment at the Bolly Department Store in Bima. 3). There is a significant effect of Dual Roles and Emotional Exhaustion on Organizational Commitment at the Bolly Department Store in Bima.